Analisis Rasio Likuiditas pada PT. Surya Citra Media, Tbk - Rahmatiar; Nurhayati; Nurul Huda (Indo Publishing, 2025)
The purpose of this study is to analyze the liquidity ratio at PT. Surya Citra Media, Tbk using Current Ratio (CR), Quick Ratio (QR) and Cash Ratio (CAR). The type of research used is descriptive. The research instrument used is a list of tables consisting of data on current assets, current liabilities, inventory, cash and cash equivalents of PT. Surya Citra Media, Tbk for 10 years, namely from 2014 to 2023. The population used in this study is all financial reports of PT. Surya Citra Media, Tbk since it was listed on the IDX from 2002 to 2023, namely for 21 years. The sample in this study is the financial report of PT. Surya Citra Media, Tbk for 10 years, namely from 2014 to 2023. The sampling technique used in this study is purposive sampling. Data were collected by means of documentation and literature study. The data analysis technique in this study is by using data analysis per component of financial ratios used to measure liquidity reflected by the Current Ratio (CR), Quick Ratio (QR) and Cash Ratio (CAR) and one-tailed t-test data analysis (t-test One Sample). The results of the study indicate that the Current Ratio (CR), Quick Ratio (QR) and Cash Ratio (CAR) at PT. Surya Citra Media, Tbk are healthy.